THE INFLUENCE OF PRUDENCE AND EARNINGS PERSISTENCE ON EARNINGS RESPONSE COEFFICIENT WITH FINANCIAL FLEXIBILITY AS A MODERATING VARIABLE - Arya Darmawan; Titik Aryati; Muna Norkhairunnisak Ustadi (International Journal of Contemporary Accounting, 2024)
This study aims to test and analyze whether prudence affects the earnings response coefficient, whether earnings persistence affects the earnings response coefficient, whether financial flexibility can moderate the influence of prudence on the earnings response coefficient, and whether financial flexibility can moderate the influence of earnings persistence on the earnings response coefficient. The sampling method used in this study is purposive sampling. The research sample consists of 59 basic material sector companies listed on the Indonesia Stock Exchange (BEI) over the past 4 years from 2019 to 2022, totaling 236 data points. The results of the study indicate that prudence significantly affects the earnings response coefficient, while earnings persistence does not significantly affect the earnings response coefficient. Financial flexibility as a moderating variable also does not have a significant influence in moderating the effects of prudence and earnings persistence on the earnings response coefficient. For future model improvements, it is necessary to calculate the ERC values for each company differently each year by reducing the time period level in the calculation, using daily data. This will result in monthly CAR data, which will then be used to estimate ERC values for specific years using monthly CAR data. Companies are advised to focus on implementing prudence principles in their financial reporting. By providing more accurate and transparent information, companies can enhance investor trust and, in turn, strengthen market responses to their reported earnings.